Optimizing employee performance through E-HRM: Insights from its organizations in Trivandrum - John, Anu P; Velmurugan, V. P. (Edelweiss Applied Science and Technology, 2024)
Electronic Human Resource Management (e-HRM) influences digital platforms to streamline and improve HR operations like hiring, managing performance, and employee self-service. This technological advancement promises significant improvements in operational efficiency and effectiveness across various HR activities. The importance of e-HRM's impact on employee performance is becoming more widely acknowledged, particularly in dynamic sectors like Information Technology (IT). The effectiveness of e-HRM systems in improving employee outcomes centred on their ability to automate HR processes, provide real-time access to critical information, and facilitate personalized support. These advancements contribute to a more responsive and supportive work environment, which in turn enhances employee satisfaction and performance. This study explores the relationship between e-HRM practices and employee performance in IT firms located in Trivandrum, focusing on how these digital tools influence employee satisfaction and overall job effectiveness. By analyzing various e-HRM strategies and their implementation, the research reveals a substantial association between well-executed e-HRM practices and enhanced employee performance. These results highlight the significance of integrating e-HRM solutions effectively to achieve improved employee engagement, productivity, and satisfaction. This research contributes valuable insights into optimizing e-HRM systems to drive organizational success and employee well-being.